Make it easier: A narrative review of dual-career empirical studies (Hacerlo más fácil: Una revisión narrativa de estudios empíricos sobre carrera dual) - Gonçalves Soares, Antonio Jorge (2020)
A dual career is a challenge faced by many athletes, who have to compaginate their sports training with the dedication required for study, work, or both. A narrative review was conducted to identify and analyze barriers to and resources for the routine of elite athletes. Eleven databases available in the Capes Journal Platform (Portal Capes) were searched using the keywords «dual career» and «athletes,» written in English, Spanish, or Portuguese. Twenty-two articles that met the established inclusion criteria and categories based on the characteristics of their samples were analyzed. The analysis showed that athletes’ difficulty in organizing a routine to meet the requirements of the educational and sports fields was the main issue regarding the conciliation of their dual careers. Among the cited sports programs, there was some success regarding time management for sports practice; however, there was a lack of in-depth analysis of the reach of these services, and elite athletes lacked a more balanced adherence to university routine. Beside the objective dimensions of dual-career management, we highlighted the importance of new lines of investigation that analyze the life projects of both athletes and their relatives in different cultures and socioeconomic realities.